2007
DOI: 10.1074/jbc.m701653200
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis-associated Conformational Changes Revealed by Human CD38 Complexed with a Non-hydrolyzable Substrate Analog

Abstract: Cyclic ADP-ribose (cADPR) is a calcium mobilization messenger important for mediating a wide range of physiological functions. The endogenous levels of cADPR in mammalian tissues are primarily controlled by CD38, a multifunctional enzyme capable of both synthesizing and hydrolyzing cADPR. In this study, a novel non-hydrolyzable analog of cADPR, N1-cIDPR (N1-cyclic inosine diphosphate ribose), was utilized to elucidate the structural determinants involved in the hydrolysis of cADPR. N1-cIDPR inhibits CD38-catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 44 publications
2
49
1
Order By: Relevance
“…This observation was also seen in the structures of human CD38, the homolog of Aplysia cyclase. [18][19][20] The results represent the first time ever that a fully active Aplysia cyclase has been observed with an NAD + molecule, its natural substrate, or an NGD + molecule, a close analog of NAD + , bound at the active site. The results also validate our approach of selecting crystals with multiple cyclase molecules in the asymmetric unit for analysis.…”
Section: Overview Of Complex Structuresmentioning
confidence: 87%
See 1 more Smart Citation
“…This observation was also seen in the structures of human CD38, the homolog of Aplysia cyclase. [18][19][20] The results represent the first time ever that a fully active Aplysia cyclase has been observed with an NAD + molecule, its natural substrate, or an NGD + molecule, a close analog of NAD + , bound at the active site. The results also validate our approach of selecting crystals with multiple cyclase molecules in the asymmetric unit for analysis.…”
Section: Overview Of Complex Structuresmentioning
confidence: 87%
“…14 To decipher details of the cyclization reaction by Aplysia cyclase and to understand the structural differences conferring its homolog human CD38 to be more of an NAD + hydrolase than cyclase (i.e., converting NAD + to a linear ADPR instead of the cyclic product, cADPR), we have performed extensive kinetic crystallographic studies to attempt to arrest the reaction at specific steps. 12,13,[15][16][17][18][19][20][21] In most cases, the crystals of both proteins contained two molecules per asymmetric unit, and even though different states of the reaction intermediate can be captured in the two molecules, it could not provide us with a comprehensive picture about the progress of the reaction. Interestingly, Aplysia cyclase and human CD38 have the ability to crystallize in different crystal forms, some of which contain multiple subunits of the protein in the asymmetric unit.…”
Section: Introductionmentioning
confidence: 98%
“…More recently, the crystal structure of the human CD38 enzymatic domain complexed with cADPR and with its analog cyclic GDP-ribose and NGD at different resolutions indicated that the binding of cADPR (or cGDPR) to the active site induces significant structural rearrangements in the dipeptide Glu146-Asp147 (217). This provides direct evidence of a conformational change at the active site during catalysis.…”
Section: A Cd38mentioning
confidence: 96%
“…Furthermore, this is the first demonstration that CD38 is functionally involved in mAChR downstream signaling to modulate electrical membrane properties of neuronal tumor cells. When we examine with a catalytically dead mutant of CD38 such as an amino acid substitution from glutamic acid 226 to glycine (Munshi et al, 2000;Liu et al, 2007), our hypothesis would be strengthened.…”
Section: Discussionmentioning
confidence: 76%